2004
DOI: 10.1161/01.hyp.0000131659.27081.19
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Tamoxifen Modulate Cerebrovascular Tone in Ovariectomized Female Rats

Abstract: Abstract-Postmenopausal estrogen deficiency increases the incidence of cerebrovascular disease. However, hormone replacement therapy is associated with an increased cardiovascular risk. Tamoxifen is a selective estrogen receptor modulator with estrogenic effects on cardiovascular risk factors, but its long-term impacts on cerebral vasculature are unknown. We hypothesized that chronic 17␤-estradiol or tamoxifen treatment exerted similar effects in reducing cerebrovascular tension in ovariectomized rats. We ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
2
20
2
Order By: Relevance
“…Similarly, the ability of TAM to potentiate vasoconstrictor effects in the mesenteric vasculature appear to be completely reversed in that BP actually decreased. Conversely, other work has shown TAM and estrogen to have no significant effects on BP in an ovariectomized rat model (38). In contrast to our study, that experiment was performed using a subcutaneous pellet to administer the hormone instead of gavage treatment, which may account for the discrepancies with our study.…”
Section: Discussioncontrasting
confidence: 85%
“…Similarly, the ability of TAM to potentiate vasoconstrictor effects in the mesenteric vasculature appear to be completely reversed in that BP actually decreased. Conversely, other work has shown TAM and estrogen to have no significant effects on BP in an ovariectomized rat model (38). In contrast to our study, that experiment was performed using a subcutaneous pellet to administer the hormone instead of gavage treatment, which may account for the discrepancies with our study.…”
Section: Discussioncontrasting
confidence: 85%
“…Other studies have demonstrated that tamoxifen reduces the mRNA expression of the α 1C subunit of the L-type Ca 2+ channel in the absence of estrogen and augments the mRNA expression of voltage-dependent potassium channels (K v ), thus possibly contributing to the vasodilatory response (38).…”
Section: Discussionmentioning
confidence: 99%
“…2,[15][16][17] Vascular contraction is greater in blood vessels of intact male than intact female rats, not different between castrated and intact males, but greater in ovariectomized (OVX) than intact females. 18,19 Also, estrogen replacement in OVX female rats restores the vascular contraction to its level in intact females, 3 suggesting that the gender differences in vascular contraction may involve direct effects of estrogen on specific hormone receptors in the vasculature.…”
Section: Gender Differences In Vascular Reactivitymentioning
confidence: 99%
“…1,2 Experimental and initial clinical data have suggested that hormone replacement therapy (HRT) may reduce cardiovascular disease in postmenopausal women. [3][4][5][6] On the other hand, reports from Heart and Estrogen-Progestin Replacement Study (HERS), HERS2, and Women's Health Initiative (WHI) clinical trials did not support vascular benefits of HRT in postmenopausal women. 1,7,8 However, the lack of beneficial effects of HRT could be explained by the small number of subjects studied and that subjects were mainly elderly women.…”
mentioning
confidence: 99%